A Conservation Law for G/G/m Queueing Systems - Bolch, Gunter; et al. (Acta Informatica, 1978)
Conservation laws are useful in the investigation of physical systems. There exists a special conservation law for priority queueing systems: a preferential treatment given to one class of jobs is afforded at the expense of other jobs. This fundamental relationship has been proved previously for G/G/1 queueing systems. In the present paper the conservation law is extended to G/G/m queueing systems and a useful application of this extension is given. © 1978 Springer-Verlag.
UnivIS-Import:2015-03-05:Pub.1978.tech.IMMD.IMMD5.aconse